Synthesis of mass exchange network for batch processes - part 1: utility targeting - Foo, Dominic Chwan Yee; Abd. Manan, Zainuddin; Yunus, R. M.; Abdul Aziz, Ramlan (2004)
Synthesis of optimal mass exchange network (MEN) for continuous processes based on Pinch Analysis has been rather well established. In contrast, very little work has been done on mass exchange network synthesis (MENS) for batch process systems. The batch process systems referred to in this work can be defined as processes which operate discontinuously and deliver the product in discrete amounts, with frequent starts an stops. There is a clear need to develop a MENS procedure for batch process systems which are industrially very common as well as important. Techniques developed in this paper for the batch MENS involved the first key steps in the synthesis task, i.e. setting the utility targets ahead of batch MEN design. The utility-targeting approach employs the vertical and horizontal cascading approaches in a newly developed tool, i.e. time-dependent composition interval table that has been adapted from heat exchange network synthesis for batch processes. Prior to MEN design, the targeting procedure establishes the minimum utility (solvent) and mass storage targets for a maximum mass recovery network. These targets are essential for network design and batch process rescheduling.